Optimization by design patterns and static analysis of web applications for a sharp adaptation of e-business start-ups in the city of Lubumbashi in DR Congo (Nesher) - FYAMA , Blaise; KADIATA , Freddy (Revue Internationale du Chercheur, 2021)
Due to some limitations of imperative development approaches, in recent years, many companies have introduced object-oriented technology into their software developments. The component paradigm, which advocates the assembly of autonomous and reusable software bricks, is indeed an interesting proposition for reducing development and maintenance costs while increasing the quality of applications. Whatever development paradigm we find ourselves in, it is essential for architects and developers alike to assess what they produce in order to produce software capable of meeting user needs, which is why we propose in this article article an approach based on the static analysis of the software and the use of some software engineering model such as the design pattern of which we note the notable impact of the latter on the regulation of certain metric parameters to acceptable thresholds and thus optimize the internal and external quality of the software.